Fixed Point Theorem in 2-Normed Spaces - Francis Yunito Rumlawang (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2020)
In this paper we prove a fixed point theorem in a complete 2-normed Spaces. We define a norm derived from 2-norm. To get the theorem proved we first study some convergent and Cauchy sequences, and contractive mappings in 2-normed spaces.